2009
DOI: 10.1088/0953-8984/21/10/104215
|View full text |Cite
|
Sign up to set email alerts
|

Overlap population diagram for ELNES and XANES: peak assignment and interpretation

Abstract: This article reviews overlap population (OP) diagrams for electron energy loss near-edge structure (ELNES) and x-ray absorption near-edge structure (XANES). By using the OP diagrams, peaks in ELNES and XANES of MgO, ZnO, AlN, GaN, InN, and YBa(2)Cu(3)O(7-x) are interpreted in terms of cation-anion and cation-cation interactions. Common features are found in the OP diagrams for different edges. A reconstruction of the unoccupied electronic structure is demonstrated by aligning the different edges with the commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…8.11. Using this OP diagram, the relationships between the spectral features and the materials properties can also be found, such as the relationships with the interface strength (Mizoguchi et al, 2006b) and electron effective mass (Mizoguchi, 2009(Mizoguchi, , 2011. This is an important advance in the interpretation of EELS.…”
Section: Interpretation Of Elnes By Overlap Population Diagrammentioning
confidence: 99%
See 1 more Smart Citation
“…8.11. Using this OP diagram, the relationships between the spectral features and the materials properties can also be found, such as the relationships with the interface strength (Mizoguchi et al, 2006b) and electron effective mass (Mizoguchi, 2009(Mizoguchi, , 2011. This is an important advance in the interpretation of EELS.…”
Section: Interpretation Of Elnes By Overlap Population Diagrammentioning
confidence: 99%
“…Beyond the reproduction, an overlap population (OP) diagram was recently proposed for the peak assignments. The OP diagram is sometimes called the COOP (crystal orbital overlap population) diagram (Hoffmann, 1987), and a combination of band structure calculations with the OP diagram was recently proposed as a powerful method to interpret ELNES (Mizoguchi, 2009;Mizoguchi et al, , 2006c. As described above, it is clearly seen that ELNES can be calculated by introducing the core-hole correctly.…”
Section: Interpretation Of Elnes By Overlap Population Diagrammentioning
confidence: 99%
“…By using this OP diagram, each peak can be assigned to be combinations of bonding and anti-bonding interactions. For instance, in the Al-K edge, it is found that peak A K is mainly composed of Al*3p-N (1), (2) anti-bonding interactions. Strong Al*-Al and Al*-N (2) anti-bonding interactions were commonly found at peak C K , and peaks B K and D K are mainly composed of strong Al*-Al and Al*-N (1) anti-bonding interactions [ Fig.…”
Section: Beyond "Reproduction"mentioning
confidence: 99%
“…2(a)]. In Al-L 2,3 edge, peak A L is composed of Al*s-N (1), (2) anti-bonding interactions and Al*d-N (1), (2) bonding interactions, the contribution of Al*s,d-N (1) and Al*d-Al anti-bonding interactions are more significant at peak B L , and strong Al*-Al anti-bonding interactions appear around peak D L [ Fig. 2(c) .…”
Section: Beyond "Reproduction"mentioning
confidence: 99%
See 1 more Smart Citation